Transformations of the sectoral structure of the region as a response to the dynamics of international trade during the pandemic - S. M. Vasin; L. A. Gamidullaeva (Модернизация, инновация, развитие, 2023)
Purpose: is to identify patterns in the regional industrial structure dynamics in response to the changing nature and volume of the region's export-import operations due to the sudden impact of the COVID-19 pandemic.Methods: general scientific methods were used: the method of monitoring changes in the socio-economic system during the COVID-19 pandemic; the description method, including a system for collecting and presenting data; the analysis method for identifying and studying stages of the process of socio-economic system transformation in the context of their changes under the influence of epidemiological factors. In addition, special methods of grouping, collecting and economic-statistical analysis of data, Gatev coefficient method for calculating structural shifts, and others are used.Results: firstly, it was determined that the most stable sectoral structure during the pandemic was presented by subjects with a high bilateral economic openness (a high level of both export and import quotas). In most of the subjects of the group, the sectoral structure changed slightly both in the first and in the second year of the pandemic. Secondly, subjects with a higher level of imports were characterized by greater stability of the sectoral structure during the pandemic: despite the higher level of dynamics of the sectoral structure, the differences over the years are not high. Thirdly, it was found that the subjects with a low level of import quotas, regardless of the level of export quotas, were the least stable sectoral structure during the pandemic: the sectoral structure of the subjects was significantly transformed.Conclusions and Relevance: to increase the resilience of the regional economy to unpredictable shocks, it is necessary to expand exportimport contacts with a long-term increase in international trade, strengthen and stabilize existing trade relations with foreign organizations along the lines of regional strengths, and it is also necessary to strengthen the position of regional production in domestic consumption.